Knowledge, attitude, and practices (KAP) of smallholder farmers towards cassava production in Limpopo, Mpumalanga and Kwazulu-Natal, South Africa - Makhura, Moraka N. (University of Pretoria, 2024)
Mini Dissertation (MSc Agric (Agricultural Economics))--University of Pretoria, 2024.